Economics of Collection and Marketing of Schizostachyum dullooa (Gamble) Majumdar from Manipur and Mizoram - Bisht, N. S. (Indian Forester, 2010)
Schizostachyum dulloo occurs naturally in large quantity in Manipur, Meghalaya and Mizoram. Due to its thin walled long internodes, this bamboo is extensively used for making kite frames. Large number of people are involved in cultivation, collection, value addition and marketing of this bamboo in these states. In the present paper, the economics of the collection, value addition, marketing and profit margin of the middlemen has been discussed in detail in Jiribam area of Manipur and Buhchang area of Mizoram and suitable interventions have been suggested for economic benefit of bamboo growers, collectors and processore.